Data-Driven E-commerce Techniques and Challenges in the Era of the Fourth Industrial Revolution - Norian, Joma H.; Jama, Abdelazez M.; Eltaieb, Mohammed H.; Adam, Ali A. (Universitas Negeri Semarang, 2020)
The E-commerce industry has a significant role in the national and international economy. E-commerce is vital in the implementation of the fourth industrial revolution, where information and communication technologies are tools in creating digital channels of trade. Understanding e-commerce is essential for it is development. The objective of this paper is to explore the popular techniques and data sources of e-commerce in addition to the current challenges that face e-commerce in the last five years. We used a literature review as a method for this research.Â According to the literature, sales records are the most popular data source used in the research community for e-commerce analytics, then followed by big data and social media. Besides, detecting and predicting customer behavior is the most used technique in e-commerce research followed by personalized recommendations. Also, we reported the main three challenges that face researchers in the field of e-commerce currently: First, e-commerce Security and privacy is a major concern for consumers and industries. Second, understanding the collected data from e-commerce systems and how to create business value from it efficiently. Third, providing personalized offers with the most appropriate items, still a difficult task.